High-performance CuNiSiCr alloy vacuum precision die-casting part and production method

Through vacuum precision die-casting process, the cold rolling and solid solution treatment are eliminated, and the rapid molding and uniform grain distribution of Cu-Ni-Si-Cr alloys are achieved, solving the problems of complex and low efficiency of traditional copper alloy manufacturing processes, and significantly improving the alloy mechanical properties and production efficiency.

CN119120964AActive Publication Date: 2024-12-13SONGSHAN LAKE MATERIALS LAB +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411032830.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2024-12-13
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

The traditional manufacturing process of high-performance copper alloys is complex and inefficient, especially when it needs to be cold rolled and solid solution treatment, resulting in long production time and uneven grains.

Method used

The vacuum precision die-casting process is adopted to eliminate cold rolling and solid solution treatments, and through vacuum induction smelting, mold preheating, casting die-casting and aging heat treatment, rapid molding and uniform grain distribution are achieved, and the conductivity is not lost while improving mechanical properties.

Benefits of technology

The preparation speed and production efficiency of Cu-Ni-Si-Cr alloy are greatly improved, the grain is refined, the second phase is evenly distributed, and the mechanical properties are significantly improved, achieving near-net forming of high-performance copper alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120964A_ABST
    Figure CN119120964A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part and a production method thereof, the steps S0 to S4 are completed within 5 minutes, copper alloy melt is poured into vacuum auxiliary die-casting equipment and injected into a die cavity of the vacuum auxiliary die-casting equipment, the injection pressure maintaining time is 20-30 seconds, then demolding is performed, and the high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part is obtained. According to the method, the high-performance Cu-Ni-Si-Cr alloy vacuum precision part is directly obtained, near-net forming of the high-performance Cu-Ni-Si-Cr alloy vacuum precision part is achieved, cold rolling treatment and solution treatment are omitted, the preparation speed and the production efficiency are greatly improved, the size of a second phase is decreased, distribution is more uniform, crystal grains are in a quasi-equiaxed crystal shape and are fine, and the high-performance Cu-Ni-Si-Cr alloy vacuum precision part is obtained. And the size of the second phase is reduced, the distribution is more uniform, and the mechanical property is greatly improved on the premise of keeping no loss of the electric conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance Cu-Ni-Si-Cr alloy die-casting parts, and in particular to a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part and a production method thereof. Background Art

[0002] High-performance copper alloys have attracted widespread attention due to their high strength and acceptable conductivity. High-performance copper alloys play an important role in the automation and electronics industries. However, the production process of high-performance copper alloys includes casting, homogenization, solution treatment, cold rolling, aging treatment, stamping and machining. The traditional manufacturing of high-performance copper alloys requires a complex process flow, so it is necessary to improve it. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a Cu-Ni-Si-Cr alloy and a production method, which eliminates cold rolling and solution treatment, greatly improves the preparation speed and production efficiency, and makes the grains quasi-equiaxed and fine, and the size of the second phase becomes smaller and the distribution is more uniform, and the mechanical properties are greatly improved while maintaining the conductivity without loss.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] A method for producing high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting parts, comprising the following steps:

[0006] Step S0, alloy smelting treatment, the metal raw material is first smelted by a vacuum induction melting method to obtain a copper alloy melt, the mass percentage of each component of the metal raw material is 3-4% nickel, 0.5-0.8% silicon, 0.2-0.3% chromium, and the balance is copper;

[0007] Step S1, vacuum preheating treatment of the mold, vacuumizing and preheating the cavity of the vacuum die-casting mold, preheating the mold to 250-280°C, and reducing the vacuum degree of the cavity to below 50Pa;

[0008] Step S2, pouring die-casting treatment, pouring the copper alloy melt obtained in step S0 into the injection cavity of the vacuum-assisted die-casting equipment, and then casting the copper alloy melt in the injection cavity into the cavity of the vacuum die-casting mold through the vacuum-assisted die-casting equipment, and the die-casting pressure is maintained at 220-280 MPa;

[0009] Step S3, forming treatment, after maintaining pressure for 20-30 seconds in step S3, the mold is opened, and a semi-finished copper alloy die-casting is obtained after demolding, so that the copper alloy die-casting is rapidly solidified in the atmosphere and forms a supersaturated solid solution, the alloy grains are refined and present a quasi-equiaxed morphology, and finally a uniformly distributed average grain size of 15±0.5μm is obtained.

[0010] Step S4, aging heat treatment, aging treatment is performed on the semi-finished vacuum die-casting part, so that the secondary phase particles precipitated simultaneously in the copper matrix include a micron-level strengthening phase with an average size of 1.1±0.5μm and a nano-level strengthening phase with an average size of 8±0.5nm, thereby obtaining a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part.

[0011] For die-cast parts with a total mass of less than 10Kg, steps S0 to S3 are completed within 5 minutes, and near-net forming of high-performance Cu-Ni-Si-Cr alloy vacuum precision parts is achieved.

[0012] In a further technical solution, the copper is selected from high-purity cathode copper with a purity of 99.99%, the nickel is selected from high-purity nickel beads with a purity of 99.99%, the silicon is selected from high-purity silicon wafers with a purity of 99.99%, and the chromium is selected from high-purity chromium particles with a purity of 99.9%.

[0013] The Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part is Cu-3.18Ni-0.75Si-0.28Cr in terms of mass percentage.

[0014] In a further technical solution, in step S4, the size of the phase particles of the precipitated nanoscale reinforcement phase is 8 nm, and the spacing between the precipitated phases of the nanoscale reinforcement phase is 10 nm.

[0015] In a further technical solution, in step S4, the precipitated secondary phase particles are nanoscale phase particles of δ-Ni2Si phase, and the orientation relationship between the δ-Ni2Si phase and the Cu matrix is ​​expressed as

[110] Cu ||

[100] δ .

[0016] In a further technical solution, the high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting parts have a spherical second phase with an average size of 1.1±0.5 μm and a short rod second phase with an average length of 2.3±0.4 μm evenly distributed in their structure.

[0017] In a further technical solution, the total die-casting time from the alloy smelting process in step S0 to the molding process in step S3 and the injection holding time of the molding process in step S3 are controlled relative to the total weight of the total mass of the die-cast part according to the following corresponding relationship:

[0018] The total weight of the die-cast parts is less than 1kg, the total die-casting time is 2 minutes, and the molding process injection and pressure holding time is 10 seconds.

[0019] The total mass of the die-cast parts is 1-5kg, the total die-casting time is 3 minutes, and the molding process injection holding time is 15 seconds.

[0020] The total weight of the die-cast parts is 8-10kg, the total die-casting time is 5 minutes, and the molding process injection holding time is 20 seconds.

[0021] The total weight of die-cast parts is 10-30kg: the total die-casting time is 5-6 minutes, and the molding process injection holding time is 25 seconds.

[0022] The total mass of die-cast parts is 30-50kg: the total die-casting time is 6-8 minutes, and the molding process injection holding time is 30 seconds.

[0023] In a further technical solution, in step S1, the mold is preheated to 260° C. and the vacuum degree of the cavity is reduced to below 30 Pa;

[0024] In the step S2, the pouring temperature of the copper alloy melt is controlled at 1250°C, the die-casting pressure of the copper alloy melt is controlled at 220MPa, fast shot die-casting is used in the middle and early stages of die-casting, and the fast shot speed of the fast shot die-casting is controlled at 1.6m / s, and slow shot die-casting is used in the later stages of die-casting, and the slow shot speed of the slow shot die-casting is controlled at 0.3m / s.

[0025] In a further technical solution, the die casting pressure of step S2 and the injection holding time of step S3 are set and controlled.

[0026] The solute diffusion coefficient D and the die casting pressure P are set according to the following formula:

[0027]

[0028] In the formula, P is the die casting pressure, D is the solute diffusion coefficient, R is the gas constant, T is the temperature, δ is the atomic free path length, η0 is the viscosity of the melt at normal pressure, and V0 is the initial volume of the liquid phase;

[0029] At the same time, the grain growth rate U is set according to the following formula to control the copper alloy melt to maintain a high cooling rate during the solidification forming process and keep it in a non-equilibrium state, so as to promote solid solution, limit grain growth and refine secondary phase particles.

[0030]

[0031] In the formula, U is the grain growth rate, f is the interface coefficient factor, D is the solute diffusion coefficient, ΔG is the free energy difference between the two phases, R is the gas constant, T is the temperature, and a is the distance between atoms.

[0032] In a further technical solution, the step S2 adopts a rapid pressurized filling counter-gravity casting method, and the copper alloy molten liquid injected into the vacuum die-casting mold is filled from the bottom of the cavity by vacuum-assisted die-casting equipment and rapidly pressurized to the top of the cavity, so that the high-temperature melt is in continuous contact with the inner wall of the mold that has just been cooled during the upward movement of the copper alloy molten liquid, thereby increasing the heat transfer rate and accelerating the cooling rate;

[0033] The heat exchange between the die-casting part and the cavity interface is set and controlled by the following formula, and the injection holding time t is set to 20S.

[0034]

[0035] In the formula, h is the interface heat transfer coefficient, Q is the heat passing through the interface, q is the interface heat flux, A is the contact area between the die casting and the cavity, t is the injection holding time, and ΔT is the temperature difference between the die casting surface and the cavity surface.

[0036] A Cu-Ni-Si-Cr alloy vacuum precision die-casting part is prepared according to the above-mentioned production method of a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part. The Cu-Ni-Si-Cr copper-gold vacuum precision die-casting part is Cu-3.18Ni-0.75Si-0.28Cr wt.% by mass.

[0037] The advantages of the present invention compared with the prior art are:

[0038] 1. The two important steps of cold rolling and solid solution in the traditional copper alloy preparation process are omitted. Vacuum die casting is used and its sub-rapid solidification characteristics are utilized to make the die-cast alloy in a high solid solution state, and the second phase is precipitated by direct aging treatment to improve the alloy performance.

[0039] 2. Realize rapid preparation and complete alloy forming within five minutes, greatly improving production efficiency.

[0040] 3. Compared with traditional casting alloys, the grain size of the vacuum die-casting alloy of the present invention is significantly refined, the size of the second phase becomes smaller, and the distribution is more uniform.

[0041] 4. The vacuum die-casting of the present invention eliminates the dendrite segregation phenomenon produced during casting, so that the alloy elements are evenly distributed, which is conducive to the uniform precipitation of the second phase during the subsequent aging treatment and improves the overall performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is the grain metallographic diagram of Example 1.

[0043] Figure 2 This is the grain metallographic diagram of Example 2.

[0044] Figure 3 This is the grain metallographic diagram of Example 3.

[0045] Figure 4 This is the grain metallographic diagram of Example 4.

[0046] Figure 5 This is the grain metallographic diagram of Comparative Example 1.

[0047] Figure 6 These are the optical microscopic morphologies of the samples of Example 1 and Comparative Example 1 before heat treatment.

[0048] Figure 7 The SEM morphology images and EDS element distribution images of the samples of Example 1 and Comparative Example 1 after heat treatment.

[0049] Figure 8 This is a TEM photograph of the nano-precipitated phase of Example 1.

[0050] Fig. 9 The SEM image and EDS element analysis of the segregation elements of Comparative Example 1.

[0051] Fig.10 This is a simulation diagram of the vacuum die-casting solidification process of Examples 1-4.

[0052] Fig.11 The following are the physical picture and metallographic picture of the alloy prepared in Example 1.

[0053] Fig.12 a is a schematic diagram of the formation and growth of externally solidified crystalline ESCs.

[0054] Fig.12 b Schematic diagram of temperature and grain distribution of VADC alloy.

[0055] Fig.12 c Melt cooling curves in different regions obtained by simulating the temperature field of the VADC process.

[0056] Fig.12 dSupersaturated solid solution.

[0057] Fig.12e Schematic diagram of the hindering effect of grain boundaries on electron movement. DETAILED DESCRIPTION

[0058] Example 1

[0059] A method for producing high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting parts, comprising the following steps:

[0060] The total mass of the metal raw material used is 10Kg, and then the copper alloy melt is poured into a vacuum cold chamber die-casting machine for die-casting, and steps S0 to S4 are completed within 5 minutes, and the near-net forming of high-performance Cu-Ni-Si-Cr alloy vacuum precision parts is achieved, and the finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part 1# sample is obtained, as follows,

[0061] Step S0, alloy smelting treatment, the metal raw material is first smelted by vacuum induction smelting method to obtain copper alloy melt, the mass percentage of each component of the metal raw material is: nickel 3-4%, silicon 0.5-0.8%, chromium 0.2-0.3%, and the balance is copper. Among them, copper is selected from high-purity cathode copper with a purity of 99.99%, nickel is selected from high-purity nickel beads with a purity of 99.99%, silicon is selected from high-purity silicon wafers with a purity of 99.99%, and chromium is selected from high-purity chromium particles with a purity of 99.9%.

[0062] Step S1, vacuum preheating treatment of the mold, vacuumizing and preheating the cavity of the vacuum die-casting mold, preheating the mold to 260° C., and reducing the vacuum degree of the cavity to below 30 Pa;

[0063] Step S2, pouring die-casting treatment, pouring the copper alloy molten liquid obtained in step S0 into the injection cavity of the vacuum-assisted die-casting equipment, and then casting the copper alloy molten liquid in the injection cavity into the cavity of the vacuum die-casting mold through the vacuum-assisted die-casting equipment, controlling the pouring temperature of the copper alloy molten liquid at 1250°C, and controlling the die-casting pressure of the copper alloy molten liquid at 220MPa. In the middle and early stages of die-casting, fast shot die-casting is used, and the fast shot speed of the fast shot die-casting is controlled at 1.6m / s. In the later stage of die-casting, slow shot die-casting is used, and the slow shot speed of the slow shot die-casting is controlled at 0.3m / s.

[0064] Step S3, forming treatment, after maintaining pressure for 20-30 seconds in step S3, the mold is opened, and a semi-finished copper alloy die-casting is obtained after demolding, so that the copper alloy die-casting is rapidly solidified in the atmosphere and forms a supersaturated solid solution, the alloy grains are refined and present a quasi-equiaxed morphology, and finally a uniformly distributed average grain size of 15±0.5μm is obtained.

[0065] Step S4, aging heat treatment, aging treatment is performed on the semi-finished vacuum die-casting part, so that the secondary phase particles precipitated simultaneously in the copper matrix include a micron-level strengthening phase with an average size of 1.1±0.5μm and a nano-level strengthening phase with an average size of 8±0.5nm, thereby obtaining a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part; the Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part is Cu-3.18Ni-0.75Si-0.28Cr in mass percentage.

[0066] Specifically, the size of the precipitated nano-scale strengthening phase particles is 8 nm, and the spacing between the precipitated nano-scale strengthening phase particles is 10 nm. The precipitated secondary phase particles are nano-scale phase particles and are δ-Ni2Si phases. The orientation relationship between the δ-Ni2Si phase and the Cu matrix is ​​expressed as

[110] Cu ||

[100] δ The crystals of the high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting parts are uniformly distributed with a second phase in the shape of a sphere with an average size of 1.1±0.5 μm and a second phase in the shape of a short rod with an average length of 2.3±0.4 μm.

[0067] Example 2

[0068] The production process of this embodiment is the same as that of embodiment 1, except that in step S2, the pouring temperature of the copper alloy melt is controlled at 1150°C to prepare a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part 2# sample. At this time, a larger pressure chamber pre-crystallization structure ( Figure 2 ).

[0069] Example 3

[0070] The production process of this embodiment is the same as that of embodiment 1, except that in step S2, the pouring temperature of the copper alloy melt is controlled at 1200°C to prepare a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part 3# sample, at which time a larger pressure chamber pre-crystallization structure ( Figure 3 ).

[0071] Example 4

[0072] The production process of this embodiment is the same as that of embodiment 1, except that in step S2, the pouring temperature of the copper alloy melt is controlled at 1300°C to prepare a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part 4# sample. At this time, a larger pressure chamber pre-crystallization structure ( Figure 4 ).

[0073] Comparative Example 1

[0074] The metal raw material is first melted by vacuum induction melting method to obtain molten metal, and the mass percentage of each component of the metal raw material is 3-4% nickel, 0.5-0.8% silicon, 0.2-0.3% chromium, and the balance is copper. The molten metal is then poured into a steel mold and cooled with the furnace (8 hours), and finally the casting is subjected to solution treatment at 980°C for 2 hours and aging treatment at 500°C for 5 hours to prepare a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part 5# sample.

[0075] Physical property tests and conductivity tests were performed on samples #1 to #5. See Table 1 for sample performance test table for details.

[0076]

[0077]

[0078] Table 1 - Sample performance test table

[0079] The process of comparative example 1 is a traditional process, referred to as VAC process, and the copper alloy prepared in comparative example 1 is referred to as VAC alloy; the process of the present invention is referred to as VADC process, and the Cu-Ni-Si-Cr alloy vacuum precision die-casting part prepared in example 1 is referred to as VADC alloy.

[0080] Obviously, the entire forming cycle of the parts (VAC alloy) of the traditional casting process is at least 15 hours, while the present invention reduces the entire die-casting forming cycle of the parts (VADC alloy) to 5 minutes, greatly improving the production speed, improving production efficiency, and saving energy and reducing consumption. At the same time, the Cu-Ni-Si-Cr copper alloy vacuum precision die-casting parts prepared by the present invention have better mechanical properties, as shown in Table 1, including tensile strength, elongation and hardness, and have good electrical conductivity. This performance enhancement is mainly due to the faster solidification rate and finer grain size of the VADC alloy. Under pressure conditions, better contact is formed between the molten metal and the mold, and frequent heat exchange leads to a quenching treatment effect in the VADC alloy. This leads to the formation of an oversaturated solid solution. DA treatment causes nano-scale precipitates to precipitate in the VADC alloy, thereby improving the mechanical properties and electrical conductivity of the VADC alloy.

[0081] Due to the limitations of solid-state forming processes, especially due to the significant solidification shrinkage and limited fluidity of high-melting-point metals such as copper alloys, it is impossible to omit important steps including cold rolling and solution treatment in the existing process and directly cast to obtain high-performance copper alloy vacuum precision die-casting parts. The present invention studies the organizational evolution and performance enhancement mechanism of Cu-Ni-Si-Cr alloy under specific heat treatment conditions, simplifies the production process, and realizes the near-net forming of high-performance Cu-Ni-Si-Cr alloy vacuum precision parts. The direct aging vacuum assisted die casting process (VADC) that eliminates important steps such as cold rolling and solution treatment is used to prepare high-performance Cu-Ni-Si-Cr alloy vacuum precision parts obtained by direct casting. The process of the present invention omits the important steps of cold rolling and solution treatment in the existing casting process, and performs high-pressure die casting under vacuum environment to reduce gas inclusions in the casting, while accelerating the solidification rate of the casting. The high-performance Cu-Ni-Si-Cr alloy vacuum precision parts obtained by direct casting have smaller grain size, less porosity and more uniform composition. Fig.11 This is the actual picture and metallographic phase diagram of the vacuum-assisted die-cast Cu-3.18Ni-0.75Si-0.28Cr (wt%) alloy of Example 1.

[0082] The formation mechanism of externally solidified ESCs in VADC alloys is as follows Fig.12 As shown in a, the pre-nucleated external solidification crystals ESCs are squeezed into the cavity under pressure, and the molten metal begins to solidify around the external solidification crystals ESCs particles. Since the external solidification crystals ESCs nucleate earlier and grow longer, their size tends to be larger. Figure 1 As shown. By optimizing the casting process, a uniform grain structure of the die casting is achieved. Fig.11 The VADC process of the present invention is a counter-gravity casting process involving the rapid pressurized filling of copper alloy melt from bottom to top. During the upward movement, the hot melt is in continuous contact with the freshly cooled mold wall, which enhances heat transfer and accelerates cooling. This interaction gradually reduces the temperature of the melt. The heat transfer behavior of the die-cast part and the cavity interface can be measured by the heat transfer coefficient,

[0083]

[0084] In the formula, h is the interface heat transfer coefficient, Q is the heat passing through the interface, q is the interface heat flux, A is the contact area between the die casting and the cavity, t is the injection holding time, and ΔT is the temperature difference between the surface of the die casting and the surface of the cavity. The heat transfer coefficient quantifies the amount of heat transferred through the interface between the die casting and the cavity per unit area, per unit time, and per unit temperature gradient. This coefficient is critical in determining the efficiency of heat exchange between the casting and the cavity, thereby affecting the microstructure of the VADC alloy. This significant and rapid heat exchange results in a significant refinement of the grain size of the VADC alloy, Fig.12 b. The present invention uses numerical simulation software to simulate the temperature changes in regions I, II and III. The specific temperature field changes are as follows Fig.10 The results show that the temperature of the VADC alloy gradually increases from zone Ⅰ to zone Ⅲ. Fig.12 c. In addition, the heat transfer coefficient of VADC decreases gradually from top to bottom, resulting in a higher solidification rate at the top of the mold cavity than at the bottom. This temperature gradient results in a slightly finer grain size in the upper part of the alloy compared to the bottom of the VADC alloy. Fig.12 b and Fig.11 As shown, the VADC method therefore favors a faster heat transfer rate between the melt and the mold wall, which results in rapid quenching of the melt, thereby forming a supersaturated solid solution. Fig.12 d. The high solid solution structure leads to the decrease of the cast properties of VADC alloy. In this high-energy metastable state, direct aging treatment of VADC alloy can induce the precipitation of nano-strengthening phase, thereby improving the comprehensive properties of VADC alloy. However, due to the fine grain size of VADC alloy, the scattering effect of grain boundary on electrons increases, resulting in the decrease of electrical conductivity of VADC alloy relative to VAC alloy. Fig.12 As shown in e.

[0085] Due to the slow cooling rate of the melt, VAC alloy will have large grains with a size of more than 400μm before thermal aging treatment. Figure 5 At the same time, a coarse dendritic structure is formed in the VAC alloy of the VAC process of Comparative Example 1, which is usually accompanied by obvious microsegregation of alloy elements. Figure 5 As shown, Fig. 9 The microsegregation elements in the dendrites are Ni and Si. However, due to the extremely fast solidification speed of the VADC alloy under pressure, the grain size formed is small, about 15μm. Figure 1 shown.

[0086] Due to the slow cooling rate of VAC alloy, the size of micron-sized primary phase is larger during the solidification process of the alloy, and the size is about 4.3±0.7μm. Figure 7As shown in a. The micron-sized primary phase of the alloy prepared by the VADC process is mainly spherical, with an average size of about 1.1±0.5μm, and part of it is short rod-shaped, with an average length of about 2.3±0.4μm. Figure 7 As shown in b.

[0087] In the VADC process of the present invention, the molten alloy is forced into the mold, which accelerates solidification and minimizes the tendency of dendrite segregation, so that the grains in the VADC alloy are significantly refined and present a quasi-equiaxed morphology. Figure 1 As shown. The VADC process of the present invention achieves a higher solidification pressure P, resulting in a lower solute diffusion coefficient D, thereby maintaining the solid solution state of the alloy elements in the alloy liquid during the solidification process. During the solidification process, the pressure reduces the interatomic distance α and the diffusion coefficient D, resulting in a decrease in the grain growth rate U, which ultimately limits the grain growth and leads to grain refinement. At the same time, the high cooling rate puts the VADC alloy in a non-equilibrium state, promotes solid solution, refines the secondary phase particles, and limits grain growth. A large number of secondary phase particles are precipitated in the Cu-Ni-Si-Cr alloy after heat treatment. Compared with the VAC alloy, the micron-sized precipitated phase in the VADC alloy is smaller in size and more evenly distributed. Figure 7 The morphology and crystallographic characteristics of the nanoscale precipitation phase in the VADC alloy after thermal aging treatment are shown in Figure 2. Figure 8 As shown. Figure 8 It can be seen from the TEM bright field image that after direct aging treatment at 450℃ for 6 hours, the supersaturated solid solution precipitates secondary phase particles in the grain boundaries. There is a coherent relationship between the precipitated secondary phase particles and the matrix. The secondary phase particles cause distortion of the nearby matrix, resulting in a characteristic contrast effect. When observing the precipitated phase of the

[110] Cu band axis under the central dark field TEM image, it is found that the secondary phase particles are spherical. The size of the precipitated secondary phase particles is about 8±2nm, and the spacing between the precipitated phases is about 10nm. The fast Fourier transform (FFT) of the secondary phase particles, such as Figure 8 The results show that the nanoscale phase particles in the VADC alloy are δ-Ni2Si phase, and the orientation relationship between the δ-Ni2Si phase and the Cu matrix can be expressed as

[110] Cu ||

[100] δ The uniform and fine nano-scale precipitation phase ensures the ideal strengthening effect and ensures that the alloy has excellent mechanical properties.

Claims

1. A production method for high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting parts, Features: The following steps are included: Step S0, alloy smelting treatment, the metal raw material is first smelted by a vacuum induction melting method to obtain a copper alloy melt, the mass percentage of each component of the metal raw material is 3-4% nickel, 0.5-0.8% silicon, 0.2-0.3% chromium, and the balance is copper; Step S1, vacuum preheating treatment of the mold, vacuumizing and preheating the cavity of the vacuum die-casting mold, preheating the mold to 250-280°C, and reducing the vacuum degree of the cavity and the pressure chamber to below 50Pa; Step S2, pouring die-casting treatment, pouring the copper alloy molten liquid obtained in step S0 into the injection cavity of the vacuum-assisted die-casting equipment, and then casting the copper alloy molten liquid in the injection cavity into the cavity of the vacuum die-casting mold through the vacuum-assisted die-casting equipment, and the die-casting pressure is maintained at 220-280MPa. Step S3, forming treatment, after maintaining pressure for 20-30 seconds in step S3, the mold is opened, and a semi-finished copper alloy die-casting is obtained after demolding, so that the copper alloy die-casting is rapidly solidified in the atmosphere and forms a supersaturated solid solution, the alloy grains are refined and present a quasi-equiaxed morphology, and finally a uniformly distributed average grain size of 15±0.5μm is obtained. Step S4, aging heat treatment, aging treatment is performed on the semi-finished vacuum die-casting part, so that the secondary phase particles precipitated simultaneously in the copper matrix include a micron-level strengthening phase with an average size of 1.1±0.5μm and a nano-level strengthening phase with an average size of 8±0.5nm, thereby obtaining a finished high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part. For die-cast parts with a total mass of less than 10 kg, steps S0 to S3 are completed within 5 minutes, and near-net forming of high-performance Cu-Ni-Si-Cr alloy vacuum precision parts is achieved.

2. A method for producing a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part according to claim 1, Features: The copper is selected from high-purity cathode copper with a purity of 99.99%, the nickel is selected from high-purity nickel beads with a purity of 99.99%, the silicon is selected from high-purity silicon wafers with a purity of 99.99%, and the chromium is selected from high-purity chromium particles with a purity of 99.9%. The Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part is Cu-3.18Ni-0.75Si-0.28Cr in terms of mass percentage.

3. The method for producing a high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part according to claim 1, Features: In the step S4, the size of the phase particles of the precipitated nano-scale reinforcement phase is 8 nm, and the distance between the precipitated phases of the nano-scale reinforcement phase is 10 nm.

4. The method for producing a high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part according to claim 1, Features: In step S4, the precipitated secondary phase particles are nano-sized phase particles of δ-Ni 2 Si phase, δ-Ni 2 The orientation relationship between the Si phase and the copper matrix is ​​expressed as [110] Cu ||[100] δ .

5. The method for producing a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part according to claim 1, Features: The high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part has uniformly distributed therein a second phase in the shape of a sphere with an average size of 1.1±0.5 μm and a second phase in the shape of a short rod with an average length of 2.3±0.4 μm.

6. The method for producing a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part according to claim 1, Features: The total die-casting time from the alloy smelting process in step S0 to the molding process in step S3 and the injection holding time in the molding process in step S3 are controlled relative to the total weight of the total mass of the die-cast part according to the following corresponding relationship: The total weight of the die-cast parts is less than 1kg, the total die-casting time is 2 minutes, and the molding process injection and pressure holding time is 10 seconds. The total mass of the die-cast parts is 1-5kg, the total die-casting time is 3 minutes, and the molding process injection holding time is 15 seconds. The total weight of the die-cast parts is 8-10kg, the total die-casting time is 5 minutes, and the molding process injection holding time is 20 seconds. The total weight of die-cast parts is 10-30kg: the total die-casting time is 5-6 minutes, and the molding process injection holding time is 25 seconds. The total mass of die-cast parts is 30-50kg: the total die-casting time is 6-8 minutes, and the molding process injection holding time is 30 seconds.

7. The method for producing a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part according to claim 1, Features: In step S1, the mold is preheated to 260° C. and the vacuum degree of the cavity is reduced to below 30 Pa; In the step S2, the pouring temperature of the copper alloy melt is controlled at 1250°C, the die-casting pressure of the copper alloy melt is controlled at 220MPa, fast shot die-casting is used in the middle and early stages of die-casting, and the fast shot speed of the fast shot die-casting is controlled at 1.6m / s, and slow shot die-casting is used in the later stages of die-casting, and the slow shot speed of the slow shot die-casting is controlled at 0.3m / s.

8. The method for producing a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part according to claim 1, Features: The die casting pressure of step S2 and the injection holding time of step S3 are set and controlled. The solute diffusion coefficient D and the die casting pressure P are set according to the following formula: In the formula, P is the die casting pressure, D is the solute diffusion coefficient, R is the gas constant, T is the temperature, δ is the atomic free path length, η 0 is the viscosity of the melt at normal pressure, V 0 is the initial volume of the liquid phase; At the same time, the grain growth rate U is set according to the following formula to control the copper alloy melt to maintain a high cooling rate during the solidification forming process and keep it in a non-equilibrium state, so as to promote solid solution, limit grain growth and refine secondary phase particles. In the formula, U is the grain growth rate, f is the interface coefficient factor, D is the solute diffusion coefficient, ΔG is the free energy difference between the two phases, R is the gas constant, T is the temperature, and a is the distance between atoms.

9. The method for producing a high-performance Cu-Ni-Si-Cr alloy vacuum precision die-casting part according to claim 1, Features: In step S2, a rapid pressurized filling counter-gravity casting method is adopted, and the copper alloy melt injected into the vacuum die-casting mold is filled from the bottom of the cavity by vacuum-assisted die-casting equipment and rapidly pressurized to the top of the cavity, so that the high-temperature melt is in continuous contact with the inner wall of the mold that has just been cooled during the upward movement of the copper alloy melt, thereby increasing the heat transfer rate and accelerating the cooling rate; The heat exchange between the die-casting part and the cavity interface is set and controlled by the following formula, and the injection holding time t is set to 20S. In the formula, h is the interface heat transfer coefficient, Q is the heat passing through the interface, q is the interface heat flux, A is the contact area between the die casting and the cavity, t is the injection holding time, and ΔT is the temperature difference between the die casting surface and the cavity surface.

10. A Cu-Ni-Si-Cr alloy vacuum precision die-casting part, prepared according to the production method of a high-performance Cu-Ni-Si-Cr copper alloy vacuum precision die-casting part according to any one of claims 1 to 9, Features: The Cu-Ni-Si-Cr copper alloy vacuum precision die-casting parts are Cu-3.18Ni-0.75Si-0.28Cr by weight. %.

Citation Information

Patent Citations

  • Method for preparing Cu-Cr-Zr-Mg series copper alloy reinforced by nanoparticles

    CN101724759A

  • Copper-based alloy ingot and preparation method thereof as well as prepared copper-based amorphous alloy

    CN103866156A

  • Precipitation hardening type copper alloy and manufacturing method therefor

    JP2018076580A

  • Copper-nickel-silicon-chromium alloy

    US5028391A